Fabrication of polymer‐dispersed liquid crystals with low driving voltage based on the thiol‐ene click reaction. Issue 7 (12th April 2017) - Shi, Zhiqing; Shao, Leishan; Zhang, Yuliang; Guan, Yu; Wang, Fei; Deng, Feifei; Liu, Yawei; Wang, Yinghan
Abstract: Polymer‐dispersed liquid crystals (PDLCs) with a well‐defined polymer matrix were successfully fabricated by the thiol‐ene click reaction based on poly(ethylene glycol) diacrylate (PEGDA) and trimethylolpropanetris‐(3‐mercaptopropionate) (TMTP). UV−visible spectrophotometry, Fourier transform IR spectroscopy, SEM and polarized optical microscopy were employed to explore the PDLC films obtained. Electro‐optical properties were studied with a UV−visible spectrophotometer. It was found that the PDLC films with optimal thiol content fabricated by the thiol‐ene click reaction showed high transmittance, low driving voltage and a low memory effect. It was concluded that the driving voltage change of PDLCs with different thiol concentrations was caused by the polymerization rate and the structure of the polymer matrix. © 2017 Society of Chemical Industry Abstract : The thiol‐ene click reaction, facile and efficient, was employed to prepare polymer‐dispersed liquid crystal films with properties of low driving voltage, high maximum transmittance and low memory effect.